A Multistate Decomposition Analysis of Cesarean Rate Variations, Associated Health Outcomes, and Financial Implications in the United States - Symum, Hasan; Zayas-Castro, José L. (American Journal of Perinatology, 2021)
Objectives Cesarean rates vary widely across the U.S. states; however, little is known about the causes and implications associated with these variations. The objectives of this study were to quantify the contribution of the clinical and nonclinical factors in explaining the difference in cesarean rates across states and to investigate the associated health outcome of cesarean variations.Study Design Using the Hospital Cost and Utilization Project State Inpatient Databases, this retrospective study included all nonfederal hospital births from Wisconsin, Florida, and New York. A nonlinear extension of the Oaxaca–Blinder method was used to decompose the contributions of differences in characteristics to cesarean variations between these states. The risk factors for cesarean delivery were identified using separate multivariable logistic regression analysis for each State.Results The difference in clinical and nonclinical factors explained a substantial (~46.57–65.45%) proportion of cesarean variations between U.S. states. The major contributors of variation were patient demographics, previous cesareans, hospital markup ratios, and social determinants of health. Cesarean delivery was significantly associated with higher postpartum readmissions and unplanned emergency department visits, greater lengths of stay, and hospital costs across all states.Conclusion Although a proportion of variations in cesarean rates can be explained by the differences in risk factors, the remaining unexplained variations suggest differences in practice patterns and imply potential quality concerns. Since nonclinical factors are likely to play an important role in cesarean variation, we recommend targeted initiatives increasing access to maternal care and improving maternal health literacy.Key Points
Keywords: pregnancy; cesarean section; maternal health; Medicaid; readmission